Ring searching and aromaticity detection - Steinbeck, Christoph (Henry Stewart Talks, 2011)
Aromatic compounds, The Hueckel rule, Subtasks in chemical informatics, The Chemistry Development Kit (CDK), The Set of All Rings (SAR), The Hanser-Jauffret-Kaufmann algorithm, SAR detection in the CDK, Finding the smallest set of smallest rings (SSSR)
Reviewed at 2022/01/23